2021
DOI: 10.1016/j.hrthm.2021.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic deformation imaging unmasks global and regional mechanical dysfunction in patients with idiopathic ventricular fibrillation: A multicenter case-control study

Abstract: BACKGROUND Idiopathic ventricular fibrillation (IVF) is diagnosed in patients with sudden onset of ventricular fibrillation of unidentified origin. New diagnostic tools that can detect subtle abnormalities are needed to diagnose and treat patients with an underlying substrate.OBJECTIVE The purpose of this study was to explore echocardiographic deformation characteristics in IVF patients.METHODS Echocardiograms were analyzed with deformation imaging by 2-dimensional speckle tracking. Global and regional measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
0
8
0
1
Order By: Relevance
“…Studies have also identified cardiomyopathy gene variants in victims of sudden unexpected death with normal autopsies, with rates ranging from 2 to 12% in recent studies. 39 , 40 The mechanisms underlying ventricular arrhythmias and sudden death in such cases with cardiomyopathy gene variants without manifest cardiomyopathy remain largely unknown, possibly involving ultrastructural anomalies undetectable by routine clinical imaging 41 , 42 and/or standard autopsy as well as changes in cardiomyocyte electrophysiology and calcium-handling directly mediated by structural proteins 43 , as was elegantly demonstrated for PKP2 . 38 …”
Section: Discussionmentioning
confidence: 99%
“…Studies have also identified cardiomyopathy gene variants in victims of sudden unexpected death with normal autopsies, with rates ranging from 2 to 12% in recent studies. 39 , 40 The mechanisms underlying ventricular arrhythmias and sudden death in such cases with cardiomyopathy gene variants without manifest cardiomyopathy remain largely unknown, possibly involving ultrastructural anomalies undetectable by routine clinical imaging 41 , 42 and/or standard autopsy as well as changes in cardiomyocyte electrophysiology and calcium-handling directly mediated by structural proteins 43 , as was elegantly demonstrated for PKP2 . 38 …”
Section: Discussionmentioning
confidence: 99%
“…Investigating patients diagnosed with IVF (after adequate clinical assessment as described above) with additional echocardiographic deformation imaging could unravel supplementary findings that lead to an alternate diagnosis. Groeneveld et al compared 47 IVF patients with 47 healthy controls (age and sex-matched) and analyzed echocardiograms with deformation imaging by 2-dimensional speckle tracking (the most commonly used tool) [ 45 , 46 ]. The authors showed both global and regional echocardiographic deformation abnormalities primarily in IVF patients ( Figure 3 ).…”
Section: The Use Of Multiple Imaging Modalitiesmentioning
confidence: 99%
“…In addition, the difference in left ventricular mechanical dispersion, a measure of the heterogeneity of myocardial contraction, may represent subtle fibrosis. Again, this could have been induced by the previous cardiac arrest, but could also be a sign of unrecognized cardiac disease [ 45 ]. Additional studies are necessary to investigate these findings in larger patient cohorts and discover the exact underlying etiology.…”
Section: The Use Of Multiple Imaging Modalitiesmentioning
confidence: 99%
See 2 more Smart Citations